Preparation and Characterization of Low-Carbon Cementitious Materials Based on Soda-Residue-Activated Ground Granulated Blast-Furnace Slag: A Case Study on Cemented Paste Backfills - Qiangsheng Ren; Wenyue Qi; Qingxin Zhao; Yali Jia; Yabin Feng; Yongji Han; Ge Duan; Haotian Pang (Metals, 2023)
To investigate the issues related to significant environmental damage and poor resource utilization of soda residue (SR), the composition and microstructure of hydration products of the GGBS (ground granulated blast-furnace slag) synergistically activated by NaOH-SR are characterized by an X-ray diffraction (XRD), Fourier-transform infrared spectrometry (FTIR), thermogravimetric–differential thermogravimetric (TG-DTG) analysis, and scanning electron microscope X-ray energy dispersive spectrometry (SEM-EDS). The effect of SR proportion, activator dosage, and water-to-binder ratio on the hydration process is studied. Results indicate that the hydration products mainly include hydrated calcium chloroaluminate (3CaO·Al2O3·CaCl2·10H2O, FS), hydrated calcium aluminosilicate (Ca2Al3(SiO4)3OH, C-A-S-H), halite (NaCl), calcite (CaCO3), and C-S-H gel. With the increase in SR proportion (especially from 80% to 90%), the C-S-H gel yield decreases significantly, while the FS yield rapidly increases, and the T-O-Si (T = Al or Si) peak shifts to a higher wavenumber range (955 cm−1 to 975 cm−1). With the decrease in activator dosage (40% to 15%), the hydration reaction gradually weakens, and the FTIR band of the T-O-Si (T = Al or Si) shifts to the lower wavenumber range (968 cm−1 to 955 cm−1). Then, cemented paste backfills (CPBs) are prepared with iron tailings as the aggregate. At mass content of 75%, SR proportion of 80%, and activator dosage of 30%, the fluidity of the CPB reaches 267.5 mm with a 28-day unconfined compressive strength (UCS) of 2.4 MPa, confirming that SR- and NaOH-synergistically-activated GGBS has great application prospects in backfill mining.